Use of in-house PCR for identification of Mycobacterium tuberculosis in BACTEC broth cultures of respiratory specimens - Ana Cláudia Carvalho Gouveia; Kathleen D. Eisenach; Solange Alves Vinhas; Fabiola Karla Corrêa Ribeiro; Renata Lyrio Peres; Reynaldo Dietze; David Jamil Hadad; Moisés Palaci (Memorias do Instituto Oswaldo Cruz, 2008)
We evaluated the ability of a PCR assay to identify Mycobacterium tuberculosis complex (MTBC) from positive BACTEC® 12B broth cultures. A total of 107 sputum samples were processed and inoculated into Ogawa slants and BACTEC® 12B vials. At a growth index (GI) > 30, 1.0 ml of the 12B broth was removed, stored, and assayed with PCR. Molecular results were compared to those obtained by phenotypic identification methods, including the BACTEC® NAP method. The average times required to perform PCR and NAP were compared. Of the 107 broth cultures evaluated, 90 were NAP positive, while 91 were PCR positive for MTBC. Of particular interest were three contaminated BACTEC® 12B broth cultures yielding microorganisms other than acid-fast bacilli growth with a MTBC that were successfully identified by PCR, resulting in a mean time of 14 days to identify MTBC before NAP identification. These results suggest that PCR could be used as an alternative to the NAP test for the rapid identification of MTBC in BACTEC® 12B cultures, particularly in those that contained both MTBC and nontuberculous mycobacteria.